Developments in Aeroengines - Owen, J. Michael (Universiti Putra Malaysia Press, 2001)
This paper reviews developments in aeroengines over the past 70 years from Whittle's first turbojet engine to the current turbofans. Modern turbofan engines are now capable of producing around 440 kN (100,000 Ib) of thrust, compared with 7kN (1600 Ib) for the first turbojet engines, while over this period the specific fuel consumption has halved and the thrust-to-weight ratio has increased significantly. The performance and reliability of these engines have revolutionised both civil and military aeronautics throughout the world. Some of the technical advances that have made these developments possible are described and possible future trends are discussed.